Ethiopia's Challenge to Egyptian Hegemony in the Nile River Basin: The Case of the Grand Ethiopian Renaissance Dam. Issue 4 (1st October 2016) - Nasr, Hala; Neef, Andreas
ABSTRACT: Home to more than 160 million people, the Nile River Basin has become one of the hotspots of the global quest for food, water and energy security. Moving closer to its completion, the Grand Ethiopian Renaissance Dam (GERD) highlights the interplay between the food, water, and energy sectors and their implications on geopolitical power relations in the region. Despite Ethiopia having the highest volumetric contribution to the Nile river flow, Egypt has maintained hydro-hegemony over the basin for several decades on the basis of historical claims and colonial agreements. Egypt has stated that its volumetric share of the Nile's water is not sufficient to sustain its growing population, declaring water availability a matter of national security. However, for Ethiopia, the GERD represents a crucial moment in its development agenda, acting as both a counterhegemonic power play, as well as a means to improving the hydropower capacity of the country, and ensuring future food security. This paper explores the various hegemonic and counter-hegemonic strategies employed by Egypt and Ethiopia respectively, highlighting the various ways in which food, water, and energy concerns are intrinsic components of the asymmetric power configurations of the Nile River Basin. By navigating the debate surrounding the GERD, this paper highlights the necessity of incorporating the food, water, and energy nexus into studies of hydro-hegemony and counter-hegemony. This allows the future policy direction for nexus management and governance in the Nile River Basin to move beyond benefit sharing, instead steering towards power sharing.